Groundwater flooding hazard in river valleys of hill regions: example of the Kapos River, Southwest-Hungary - Lóczy, Dénes; Dezső, József (Hungarian Geographical Bulletin, 2013)
In the riverine floodplains of hill regions built of sand and loess, interactions between river channels and groundwater reservoirs result from the high permeability of the riverbed and the spatial heterogeneity of fl oodplain deposits and soils. Although in dry periods, groundwater sustains the river in the form of baseflow, and the relationship is the opposite during wet spells, the predictability of inundations from rising groundwater levels is rather low. Also the spatial and temporal development of inundation in narrow floodplains of hill regions (like the Kapos River fl oodplain) takes a course in several respects different from that in broad lowlands. In the study areas of the Kapos floodplain topographic, remote sensing and soil distribution surveys are jointly applied to assess the true extent of frequent inundation hazard.